3h+1=3(h+1)

Simple and best practice solution for 3h+1=3(h+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h+1=3(h+1) equation:


Simplifying
3h + 1 = 3(h + 1)

Reorder the terms:
1 + 3h = 3(h + 1)

Reorder the terms:
1 + 3h = 3(1 + h)
1 + 3h = (1 * 3 + h * 3)
1 + 3h = (3 + 3h)

Add '-3h' to each side of the equation.
1 + 3h + -3h = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
1 + 0 = 3 + 3h + -3h
1 = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
1 = 3 + 0
1 = 3

Solving
1 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 | | -6x-1=-1 | | 3(x-5)=6(x-6) | | 14x+23=-93 | | 7x+3(4x-1)=49 | | 12-8x-6=-13x+21 | | -3x-10=-10 | | 2x-4+x=8 | | (4x-7)-(2x-2)= | | -7x+5=-58 | | 64=8r+2 | | 7h=9.1 | | (2x+5x)=20 | | 6n-10=4n-2 | | 7x+2=4x+15 | | (49y)-2m=180 | | 3(x+2)=2(2x+5) | | 60+n+6=75 | | (3y+4y)*2-2m=180 | | 5(x+2)=4(2x+1) | | 7x^2+21x-70=0 | | z/114=6 | | 6x-11=1-51 | | (3y+4y)2-2m=180 | | 10=4(x-2)-(x-6) | | 125m-75m+42975=45225-175m | | 3*2x+3=21 | | 4(z-5)+6z-3= | | X+2=2-4x |

Equations solver categories